Crack formation in vacuum concrete - Yakovlev, Grigory; Khokhriakov, Nikolai (Journal of Civil Engineering and Management, 2002)
The reasons of crack formation in vacuum concrete floors with reinforcing mineral wear-resistant coating were investigated. The main reasons of crack formation are connected with low concrete strength due to the lack of water for cement hydration, the absence of shrinkage seams in floor structure, wrong reinforcement and excess thickness of strengthening mineral coating of concrete floor which initiates the crack formation. At the concrete thickness 150 mm, the depth of crack spreading was 115 mm, the concrete strength in kerns – 14.2–24.8 MPa instead of 30 MPa as planned, and the concrete macrostructure had the signs of lamination. Besides, an air clearance up to 4 mm in size was found between the foundation and concrete floor. The reinforcement skeleton structure in concrete floors did not envisage the possibility of horizontal displacement of concrete coating in the square limited by deformation seams, and the deformation seams did not penetrate into the depth planned eliminating their formation during concrete hardening. X-ray phase analysis of fresh hardening coating of concrete surface showed the presence of ettringite in it, and non- hydrated Portland cement minerals prevailed in the structure of concrete solution resulting in insufficient strength of the concrete hardened. Thus, due to the considerable heterogeneity of vacuum concrete structure and properties by thickness, the presence of the initiator of crack formation in the concrete upper layer (ettringite) and wrong reinforcing the formation of uneven shrinkage phenomena in hardening cement takes place resulting in crack net formation in the upper stretched concrete area.Frist Published Online: 30 Jul 2012